Designing a large scale solar PV system and impact analysis of its integration into Sudan power grid - Ibrahim Basheer, Omar Abdelrouf (2022)
The increasing energy demand and the development of renewable energy technology present a new possibility to implement renewable energy sources. Sudanese people have been suffering from electricity outage due to the price fluctuation in fuel resources. Unfortunately, Renewable energy power plant can cause a huge implication of grid. Many considerations should be considered to study the voltage drop and load flow analysis as well. Solar energy is the most prominent among renewable sources, as it is an inexhaustible resource and its exploitation has thus far been ecologically friendly. The aim of this project is to simulate and analyse a large-scale grid connected photovoltaic system is designed with 100 MW installed capacity. Details of the design include the total number of PV modules, inverter, cables and substation. In this study, the main system design is undertaken based on the amount of generated power. The generated output power from the PV system is at 0.8 kV voltage level. Then it connected to several transformers. The project site is at the desert in Khartoum, Sudan. The output of the power transformer is synchronized to the national grid at Khartoum substation less than 100 m of the supply point. To achieve the power ratings, 397 inverters has been designed with 24 string for each resulting at 100 MW generated power were adopted. This project used PVsyst software for energy production and ETAP software for the substation design.